Internet Use Influences Self-Related Process: Evidence From Behavior and ERPs - Zhao, Gai; Zhang, Yan; Kong, Fanchang; Liu, Zhaojun; Wang, Yadan; Zhou, Bo; Zhang, Xingjie; Tang, Feng; Zhou, Zongkui (Frontiers in Psychology, 2018)
The present study aimed to examine whether a self-related stimulus produces a self-related process bias between pathological-tendency internet users and ordinary internet users. Participants were asked to judge the color of the target stimulus’ frame (internet pictures) in an implicit priming task, which enclosed the prime of self/other-related words and the target of the online image in sequence. Results from Experiment 1 showed that the main effect of priming type and the interaction of the priming type and the subject group were significant. Further analysis revealed that response time (RT) under the self-related condition was significantly longer than that of the other related conditions. Simple effect analysis indicated that RT under the self-related condition was significantly longer than that under the other-related conditions for pathological-tendency internet users but not for ordinary internet users. In Experiment 2, behavior results demonstrated the main effects of priming type and subject group. Further analysis suggested that RT under the self-related condition was significantly longer than that in the other-related tasks for both groups, and the RT of the pathological-tendency internet users was shorter than that of ordinary internet users. ERP data showed that the amplitudes of late positive components under the self-related condition were smaller than that under the other-related conditions. The N2 amplitude was larger under the self-related condition than under the other-related conditions for pathological-tendency internet users but not for ordinary internet users. This finding suggested that internet use influenced the inhibition control and was automatically retrieved during the processing of self-related stimuli.